Viral Coagulopathy in Patients With COVID-19: Treatment and Care - Kipshidze, Nickolas; Dangas, George; White, Christopher J.; Kipshidze, Nodar; Siddiqui, Fakiha; Lattimer, Christopher R.; Carter, Charles A.; Fareed, Jawed (Clinical and applied thrombosis/hemostasis, 2020)
COVID-19 has proven to be particularly challenging given the complex pathogenesis of SARS-CoV-2. Early data have demonstrated how the host response to this novel coronavirus leads to the proliferation of pro-inflammatory cytokines, massive endothelial damage, and generalized vascular manifestations. While SARS-CoV-2 primarily targets the upper and lower respiratory tract, other organ systems are also affected. SARS-CoV-2 relies on 2 host cell receptors for successful attachment: angiotensin-converting enzyme 2 and transmembrane protease serine 2. Clinicopathologic reports have demonstrated associations between severe COVID-19 and viral coagulopathy, resulting in pulmonary embolism; venous, arterial, and microvascular thrombosis; lung endothelial injury; and associated thrombotic complications leading to acute respiratory distress syndrome. Viral coagulopathy is not novel given similar observations with SARS classic, including the consumption of platelets, generation of thrombin, and increased fibrin degradation product exhibiting overt disseminated intravascular coagulation–like syndrome. The specific mechanism(s) behind the thrombotic complications in COVID-19 patients has yet to be fully understood. Parenteral anticoagulants, such as heparin and low-molecular-weights heparins, are widely used in the management of COVID-19 patients. Beyond the primary (anticoagulant) effects of these agents, they may exhibit antiviral, anti-inflammatory, and cytoprotective effects. Direct oral anticoagulants and antiplatelet agents are also useful in the management of these patients. Tissue plasminogen activator and other fibrinolytic modalities may also be helpful in the overall management. Catheter-directed thrombolysis can be used in patients developing pulmonary embolism. Further investigations are required to understand the molecular and cellular mechanisms involved in the pathogenesis of COVID-19-associated thrombotic complications.